Client Empowerment Through Life Skills Training: A Qualitative Study at BAPAS Class II Pringsewu, Lampung - Siti Khotimatun, Siti Khotimatun; Fariza Makmun, Fariza Makmun; Zamhariri, Zamhariri; Yuberti, Yuberti; Fitri Yanti, Fitri Yanti (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores client empowerment through life skills training initiatives at Bapas Class II Pringsewu Regency, Lampung Province. The objective of the study was to determine how the life skills program empowers clients at Bapas Class II Pringsewu. A qualitative descriptive approach was used, combining a literature review with direct field observations. Data were collected through field observations, in-depth interviews with 18 informants, and document analysis. The study findings indicate that: (1) clients are actively involved in various vocational trainings, including haircutting, flower arranging, culinary skills, and sewing; (2) participants develop economically valuable skills such as creative sewing and high-quality cooking; and (3) religious education is integrated into the program, which encourages self-awareness, empathy, and ethical behavior. These initiatives significantly support client reintegration, as reflected in a decreased likelihood of recidivism and greater potential for economic independence. In conclusion, the life skills program at Bapas Class II Pringsewu demonstrates a significant impact on clients' personal and social development. Therefore, it is recommended that the government further strengthen and expand this initiative to support sustainable reintegration and prevent future offenses.